FAKTOR DETERMINAN KESIAPSIAGAAN PERAWAT GAWAT DARURAT DALAM MENGHADAPI PENYAKIT INFEKSI EMERGING - Laksmi, Ida Ayu Agung; Udaksana, I Made Adi Wahyu; Susila, I Made Dwie Pradnya (jitek, 2023)
Emerging infectious diseases are infectious diseases that appear and increase so rapidly that they can be said to be epidemics or non-natural disasters. As the front line, nurses are faced with uncertainties that increase the risk of exposure to disease, so preparedness is needed. This study aims to analyze the factors that affect the preparedness of emergency nurses in dealing with patients with emerging infectious diseases. This study is a correlational analytic study involving 109 emergency nurses in Bali. Data were collected through an online survey using a general questionnaire on demographic factors, a questionnaire on nurses' knowledge of EID, and a questionnaire on nurse preparedness in dealing with EID that had been tested for validity and reliability. The results of the bivariate analysis using the Spearman rank test showed that only the availability of personal protective equipment (p-value 0.007, p < α (0.05) and nurses' knowledge had a significant correlation with emergency nurse preparedness in dealing with patients with emerging infectious diseases (p-value 0.005, p < α (0.05). Therefore, it can be suggested to the hospital management in providing opportunities for emergency nurses to receive training related to emergencies in dealing with emerging infectious diseases and increase the assurance of the availability of adequate personal protective equipment (PPE).